RESOURCE MOBILIZATION AND EMERGENCY GOVERNANCE: A STUDY OF MADRASAH LEADERSHIP CAPABILITIES IN UTILIZING FINANCIAL AND LOGISTICS TECHNOLOGY FOR POST-DISASTERS RESPONSE - Zulkhairi; Nurasiah (CV Naskah Aceh, 2025)
The research problem focuses on the gap between the strategic potential of madrasas as community-based disaster response hubs and their actual leadership capabilities in adopting and utilizing financial technology (fintech) and logistics, which are increasingly crucial in modern emergency management. This study uses a qualitative library research method by analyzing selected literature sources from 2020-2025. The results reveal that: (1) Fintech transforms fund mobilization to be more inclusive, transparent, and fast, despite the challenges of cybersecurity and the digital divide; (2) Logistics technology (AI, IoT, blockchain, drones) creates a proactive, traceable, and agile supply chain, with success dependent on interoperability and human resource capacity; (3) Madrasa leadership capabilities in digital coordination determine their effectiveness as information and collaboration hubs; (4) Emergency pressures trigger operational governance innovations towards digital procedures and participatory real-time accountability. In conclusion, digital technology is a transformative lever, but madrasa leadership capabilities in digital convergence, integrating traditional social authority with technological competence, are a critical success factor. The implementation of the research findings recommends the establishment of a digital-based integrated response platform involving madrasas, preceded by a digital leadership capacity building program, the development of emergency protocols, and inclusive policy collaboration to build holistic disaster resilience.